2019
DOI: 10.1002/jssc.201900564
|View full text |Cite
|
Sign up to set email alerts
|

Combined biocompatible medium with molecularly imprinted polymers for determination of aflatoxins B1 in real sample

Abstract: A kind of molecularly imprinted polymers modified with biocompatible medium was prepared by suspension polymerization. The obtained hybrid materials were used as the adsorbents for the solid‐phase extraction of aflatoxins B1 in real samples. A structural analog of the target, 6‐methyl‐4‐phenylchroman‐2‐one was used as the pseudo‐template, owing to their lower toxicity and cheaper price compared with aflatoxins B1; and methacrylic acid and glycidyl methacrylate were used as the co‐monomers. Scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Iridoid glycosides, spiramycin, 2,4-dichlorophenoxyacetic acid, diclofenac, alfatoxins [17][18][19][20][21] Suspension polymerization Malachite green, p-hydroxybenzoic acid, timolol, alfatoxins B1, Pb 2+ [22][23][24][25][26] Emulsion polymerization Quercetin, malachite green, Listeria monocytogenes, triazines, Cd 2+ [27][28][29][30][31] Seed polymerization Nicotinamide, bisphenol A, promazine derivates [32][33][34] Precipitation polymerization Triclosan and triclocarban, strychnine, caffeic acid, vitamin E, prednisolone [35][36][37][38][39] RAFT polymerization Benzimidazole, propranolol, polycyclic aromatic hydrocarbons [40][41][42] Atom transfer radical polymerization Ofloxacin, ␤2-agonists [43,44] Sol-gel Iprodione, methylxanthines [45,46] RAFT: Reversible addition fragmentation chain transfer.…”
Section: Bulk Polymerizationmentioning
confidence: 99%
“…Iridoid glycosides, spiramycin, 2,4-dichlorophenoxyacetic acid, diclofenac, alfatoxins [17][18][19][20][21] Suspension polymerization Malachite green, p-hydroxybenzoic acid, timolol, alfatoxins B1, Pb 2+ [22][23][24][25][26] Emulsion polymerization Quercetin, malachite green, Listeria monocytogenes, triazines, Cd 2+ [27][28][29][30][31] Seed polymerization Nicotinamide, bisphenol A, promazine derivates [32][33][34] Precipitation polymerization Triclosan and triclocarban, strychnine, caffeic acid, vitamin E, prednisolone [35][36][37][38][39] RAFT polymerization Benzimidazole, propranolol, polycyclic aromatic hydrocarbons [40][41][42] Atom transfer radical polymerization Ofloxacin, ␤2-agonists [43,44] Sol-gel Iprodione, methylxanthines [45,46] RAFT: Reversible addition fragmentation chain transfer.…”
Section: Bulk Polymerizationmentioning
confidence: 99%
“…Several traditional polymerization approaches, including suspension [100,101], mini emulsion [102], and multistep seed swelling polymerization [103], and the new Pickering emulsion polymerization [104] were also utilized for the synthesis of spherical MIPs. For example, a kind of biocompatible dummy MIP nanoparticles prepared by suspension polymerization was used for SPE and determination of aflatoxins B1 in soy sauce without the process of protein removal [100], and a type of MIP micron spheres obtained by miniemulsion polymerization for SPE and quantification of aflatoxin M 1 and B 1 in different foods and feeds [102].…”
Section: Applications Of Molecularly Imprinted Polymer‐based Spe To Rmentioning
confidence: 99%
“…15 Reported dummy template molecules include 5,7-dimethoxycoumarin (DMC), 2 quercetin, 16 7-acetoxy-4-methylcoumarin, 17 and 6-phenyl-4-methyl-2-chromanone ( Figure 3). 18 DMC is a common template molecule for the preparation of AF MIPs.…”
Section: Af Mipsmentioning
confidence: 99%
“…Song et al 18 reported a hydrophilic MIP prepared by suspension polymerization. Glycidyl methacrylate (GMA) is employed to regulate the hydrophilicity of the polymer, and polyvinyl alcohol is used as a suspending agent ( Figure 5).…”
Section: Suspension Polymerizationmentioning
confidence: 99%